2006
DOI: 10.1191/0961203306lu2317oa
|View full text |Cite
|
Sign up to set email alerts
|

Antinucleosome Antibodies in Patients with Juvenile Systemic Lupus Erythematosus

Abstract: Our objective was to evaluate the frequency of antinucleosome antibodies (anti-Ncs) in juvenile systemic lupus erythematosus (JSLE) comparing it to that observed for anti-DNA and to correlate the presence of these antibodies with clinical manifestations and disease activity. Anti-Ncs and anti-DNA were detected by ELISA in 74 patients with JSLE and 64 normal controls. Clinical records were reviewed. Disease activity was assessed by SLEDAI score. Anti-Ncs and anti-DNA showed sensitivity of 52.7% and 54% and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
14

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
2
10
0
14
Order By: Relevance
“…On the other hand, 15 of 23 (65%) anti-dsDNA ELISA positive samples were also positive in the IgG anti-NCS and anti-CHR-60 assays, and 4% of the JSLE patients were negative in these assays. Such dissociation has been reported previously 13,38,40,42,43,[46][47][48] and indicates that these autoantibody systems have complementary roles in the diagnosis of SLE. This may have an impact in clinical practice inasmuch as the demonstration of anti-NCS antibodies in the absence of other autoantibodies may be particularly helpful in patients with few clinical manifestations (e.g.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…On the other hand, 15 of 23 (65%) anti-dsDNA ELISA positive samples were also positive in the IgG anti-NCS and anti-CHR-60 assays, and 4% of the JSLE patients were negative in these assays. Such dissociation has been reported previously 13,38,40,42,43,[46][47][48] and indicates that these autoantibody systems have complementary roles in the diagnosis of SLE. This may have an impact in clinical practice inasmuch as the demonstration of anti-NCS antibodies in the absence of other autoantibodies may be particularly helpful in patients with few clinical manifestations (e.g.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, however, the presence of antibodies against chromatin components was largely associated in the literature with markers of active lupus nephritis. Several studies have previously demonstrated an association of anti-nucleosome antibodies and disease activity or active nephritis in SLE 11,13,14,35,38,40,43,48 It has been also pointed that anti-nucleosome antibodies are highly correlated with renal failure and progression to kidney transplantation in SLE. 49 The present study confi rmed such association also for JSLE and further extended the observation to several autoantibody specifi cities within the supra-molecular chromatin system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alguns trabalhos também têm demonstrado correlação dos anticorpos AN com parâmetros conhecidos de atividade de doença. Desse modo, dois trabalhos estudando anticorpos AN em LES na população brasileira encontraram sua associação com atividade de doença, particularmente renal (20,21) . Por outro lado, Quattrocchi et al (22) , estudando anticorpos AN em 47 casos de LES e em 62 pacientes com outras colagenoses, tais como artrite reumatóide, doença mista do tecido conjuntivo, ES e síndrome de Sjögren, além de 22 controles sadios, observaram que, apesar de confirmarem a alta sensibilidade desse teste para LES, não encontraram correlação com atividade de doença em LES, avaliada pelo ECLAM.…”
Section: Methodsunclassified
“…Наряду с АНФ, при СКВ важное значение имеет выявление антител к нативной ДНК (анти-ДНК), РНП, антигену Смита (анти-Sm), анти-Ro/SS-A и анти-La/SS-B (в совокупности -так называе-мые «экстрагируемые ядерные антигены»). Согласно дан-ным литературы, при СКВ с ювенильным дебютом анти-ДНК выявляются у 54-93%; анти-Sm -у 17-52%; анти-РНП -у 22-50%; анти-Ro/SS-A -у 33-54%; анти-La/SS-B -у 14-32% больных [25][26][27][28][29][30][31][32]. С учетом более широкого спектра антител, выявляемых в детской популяции, на эта-пе диагностики СКВ с ювенильным дебютом настоятельно рекомендуется их исследование.…”
unclassified